Hollow Microneedle Arrays Produced by Low‐Cost, High‐Fidelity Replication of Hypodermic Needle Tips for High‐Dose Transdermal Drug Delivery. Issue 6 (9th February 2021) - Zhou, Cuiping; Tang, Hao; Zhang, Li; An, Hong; Wu, Yunjin; Tang, Ding; Zhou, Jianhua
Abstract : As an emerging tool for transdermal drug delivery and body fluid sampling, hollow microneedles (HMNs) exhibit advantages such as safety in use, painlessness, high drug loading, precise administration, and convenience of connecting to external devices. However, the existing techniques for fabricating HMNs are expensive and poor in batch‐to‐batch consistency. Herein, a simple, high‐fidelity, cost‐effective replication technique to produce polymeric HMN arrays using the tips of traditional hypodermic needles as the template is developed. HMN arrays of four different polymers are successfully fabricated. The as‐fabricated HMN arrays exhibit excellent consistency from batch to batch, a puncture force of ≈1.03 N for penetrating rabbit skin, almost no cytotoxicity to CT‐26.WT cells, and a maximum drug‐loading capacity of 2.06 mg cm −2 for each array. Furthermore, a bundle device is fabricated by attaching the HMN array to a looped zip tie and applied to load a protein vaccine into mice, and it is found that the vaccination efficiency of the HMN arrays is comparable to that of the traditional hypodermic injection. The experiments suggest that the replication technique proposed herein is promising for the large‐scale production of HMN arrays for cosmetics, drug delivery, minimally invasive diagnosis, etc. Abstract : A simple, low‐cost, and high‐fidelity replication strategy is developed to massly produce hollow microneedle arrays for transdermal delivery of vaccines.